PEMUNGUTAN/PENYETORAN PAJAK TRANSAKSI BENDAHARA PENGELUARAN KANTOR “X” MENGGUNAKAN INTERNET BANKING : - - joko sumantri; Fadhil Muhammad Hartomo (Jurnalku, 2021)
This study aims to determine the implementation of the tasks performed by the Expenditure Treasure of “X” Office in collecting and depositing taxes using Internet Banking and the constraints experienced. By using an exploratory method, it is known that the Expenditure Treasure of “X” Office has carried out his duties in accordance with the applicable regulations. However, during the research, it was found that there was a time when the tax collection on VAT (Value Added Tax) carried out by the Expenditure Treasure of “X” Office according to PMK Number 231/PMK.03/2019 was not implemented on time. The imposition of VAT on purchases of goods above Rp2,000,000 (two million rupiah) was implemented in June 2020 which should have started April 1, 2020. Meanwhile, in carrying out the task of depositing taxes by the Expenditure Treasure of “X” Office, server down problems and system errors still often occur at the beginning of the month and towards the end of the fiscal year. Keywords : Internet Banking, exploratory, Expenditure Treasure of “X” Office, tax payment